Editors' introduction - SADEH, N.M. (Institutional Knowledge at Singapore Management University, 2006)
This issue is composed of a special section on “Ontology-based E-Catalog in e-Commerce” and two relevant papers accepted through regular submission and review procedure. The papers from special section is guest edited by Junho Shim (Sookmyung Women’s University, Korea) and Simon S.Y. Shim (San Jose State University, USA) from the International Workshop on Data Engineering in E-Commerce (DEEC 2005) which was held in April 2005 at Tokyo Japan. For the introduction of special section, refer to the guest editor’s introduction. We would like to thank to the dedicated effort of guest editors.The papers selected for the special section concern about the ontology management for large scale e-Commerce applications, building operational product ontology system, and ontology-based e-Commerce negotiation to resolve the semantic heterogeneity problem. These issues are related with e-Catalog system. For the e-catalog, the search has been inherent problem, so an evaluation and optimization of the catalog search process of e-procurement is selected. The last paper deals with the Web Service decomposition problem and proposed a high performance cache management scheme.In addition, we have selected two papers that are relevant to the theme of special section. An efficient indexing technique for XML-based e-catalog (authored by A. Ozgur and T. Gundem) and the security framework for content-based publish-subscribe system (authored by G. Padmavathi and S. Annadurai) are selected for this issue.As usual, we would like to thank to reviewers’ dedicated effort for the review of papers that have contributed to the improvement of manuscripts in this issue.